Live‐Cell SERS Endoscopy Using Plasmonic Nanowire Waveguides. (28th May 2014) - Lu, Gang; De Keersmaecker, Herlinde; Su, Liang; Kenens, Bart; Rocha, Susana; Fron, Eduard; Chen, Chang; Van Dorpe, Pol; Mizuno, Hideaki; Hofkens, Johan; Hutchison, James A.; Uji‐i, Hiroshi
<x xml:space="preserve">Abstract</x> Live‐cell surface‐enhanced Raman spectroscopy (SERS) endoscopy is developed by using plasmonic nanowire waveguides as endoscopic probes. It is demonstrated that the probe insertion does not stress the cell. Opposed to conventional SERS endoscopy, with excitation at the hotspot within the cell, the remote excitation method yields low‐background SERS spectra from specific cell compartments with minimal associated photodamage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>